Are the strategic research agendas of researchers in the social sciences determinants of research productivity? - Santos, J. M. (2022)
This study analyzes the association between the strategic research agendas of researchers in the social sciences and their research performance. Based on a worldwide sample of 604 researchers, this study assesses whether researchers’ strategic research agendas are predictors of both short-term (last 3 years) and long-term career publications and citations, after controlling for relevant literature-informed determinants of research productivity. The results show that, in a short-term perspective, research agendas have a limited association with productivity and visibility. Solely the research agendas strategically oriented towards publishing and those collaborative in nature have positive associations with research productivity and visibility. This changes when a long-term perspective is considered. Over the course of a career, research agendas are significantly associated with number of publications and citations. Research agendas oriented towards publishing and collaboration, and those focused on a single field of knowledge, prestige gain and discovery have a positive effect on career research performance, while those research agendas that are overspecialized, dispersed over several fields of knowledge and topics, and influenced by a mentor have opposite associations. This study also finds that prolific research productivity shapes one’s strategic research agenda: the more one publishes, the more one is bound to have a strategic research agenda that is focused on prestige, discovery, a further drive to publish, engagement in a multitude of topics to research, and pursuing multidisciplinary and collaborative research. This effect is driven by an accumulation of publications, not citations. These findings highlight how strategic research choices interact with the individual performance of researchers in the social sciences in performativity-oriented research landscapes.